Evaluation of patient satisfaction with health services in University Dentistry Clinical Center of Kosovo, Europe. - FATMIR DRAGIDELLA; LULËJETA FERIZI; DONIKA DRAGIDELLA (International Journal of Pharma and Bio Sciences, 2017)
The aim of this study was to assess the level of the satisfaction among patients with dental health services provided by University Dentistry Clinical Center of Kosovo (UDCCK). This study was conducted among 150 patients. Their satisfaction regarding the quality of health care service was assessed by measuring instrument - questionnaire. Descriptive and qualitative data were analyzed using Chi-square test and Fisher’s exact test. The significance level was set up at p<0.05. Study sample was compromised by 57.3% of females and 42.7% of males. Ages of patients’ were between 18 to 65 years. According to the residence, 52.0% of respondents were from urban areas and 48.0% were from rural areas. From the obtained results, we found that 98.0% of patients are agreed with dentists’ services, 68.7% agreed with nurses’ behavior, 99.3% of patients agreed with physical facilities and 94.7% agreed with administration service. According to the results of this study, over 90% of the patients were satisfied with the dental health services offered at UDCCK.